Immunogenicity Test of ESAT-6/CFP-10 Mycobacterium Tuberculosis (Indonesian Strain) Recombinant Protein Fusion: IFN-γ and CD8+ T Cells Expression in PBMC Culture - Anung Sri Handayani; Tri Wahju Astuti; Teguh Rahayu Sartono; Maimun Zulhaidah Arthamin; Fransisca Srioetami Tanoerahardjo (Jurnal Respirologi Indonesia, 2018)
Background: BCG vaccination is one way to control tuberculosis (TB) but still poor in efficacy thus new vaccine development is needed. Immunogenicity test is needed in developing new vaccine. The aim of this study was to understand whether the recombinant protein fusion of ESAT-6/CFP-10 Mycobacterium tuberculosis (M. tuberculosis) can stimulate cellular immune response, especially IFN-γ and CD8 + T cell expression in PBMC cultures. Methods: This study was an experimental laboratory research conducted on PBMC cultures of 3 groups of subjects (TB patients, latent TB patients and healthy subjects) at RSUD Dr. Saiful Anwar in April-July 2017. The sample of each groups was 8 subjects. Each groups induced by recombinant protein fusion ESAT-6/CFP-10 M. tuberculosis as a standard protocol and to establish the immunogenicity status. CD8+ T cells IFN-γ expressed by C8+ were measured by flowcytometry. Result: Recombinant protein fusion ESAT-6/CFP-10 can stimulate CD8+ T cells and IFN-γ expressed by CD8+ T cells in all group. The highest stimulation of CD8+ percentage was found in healthy subject (37.533 ± 7.264) and IFN-γ expressed by CD8+ T cells was found in healthy subject (7.908 ± 4.457); There are increase significantly CD8+ T cells (p=0.001) and IFN-γ expressed by CD8+ T cells (p=0.217) not significantly in healthy subject compared in PPD and without antigen. Conclusion: Recombinant protein fusion ESAT-6/CFP-10 M. tuberculosis can stimulate CD8+ T cells and IFN-γ expressed by CD8+ T cells in healthy subject. Recombinant protein fusion ESAT-6/CFP-10 M. tuberculosis potential as a new vaccine candidate. (J Respir Indo. 2018;38: 210-8)